Genetic analysis ofthe tolerance to rimsulfuron in maize (zea mays l.) (2001)
Experiments were conducted on the campus of the NationalUniversity of Colombia, at Bogotá, Colombia to study thenature of genetic tolerance to rimsulfuron herbicide in maize(Zea mays L.). In a first step, sensitive and tolerant lines were selected and crossed. In a second step, two inbred lines, one tolerant ('L-34') and one sensitive ('L-31 '), were studied with their F1 F2 and backcross progenies to determine the genetic basis for tolerance to rimsulfuron in two environments. Plants were sprayed with 60 g a.i. ha" rimsulfuron. This dose caused 60% injury (visual phytotoxicity) in the sensitive lineo Visual phytotoxicity, and height and shoot dry weight reduction, both expressed as percentage of check plants, were used as indices of tolerance to rimsulfuron. Results obtained from generation mean analysis indicated that tolerance to rimsulfuron is mainly under the genetic control of additive and dominance effects. Results from the Mendelian analysis and from comparisons between parents and F1 populations derived from tolerant and sensitive inbred lines crosses, also suggest dominance effects oriented toward tolerance. All F, populations were injured less than 18% (visual phytotoxicity). The estimates ofheritabilities were in general negative. When visual phytotoxicity was used as an index of tolerance to rimsulfuron, estimate of the minimum number of segregating factors (Castle- Wright index) was 1.3.